2022
DOI: 10.1021/acs.macromol.2c00331
|View full text |Cite
|
Sign up to set email alerts
|

Wall Slip of Bimodal Polyethylene

Abstract: Cohesive slip occurs in the flow of linear polyethylene melts over high-surface-energy walls, changing both the velocity profile and the stress. The slip behavior of bimodal molecular weight distribution (MWD) polymers is different from that of unimodal MWD polymers and is not yet fully understood. Here, we study a set of four polyethylenes with a systematic change in MWD, making it possible to examine the effect of bimodal molecular weight distribution on the slip behavior. The results show that slip in simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The tube-model parameters calculated for our material are used to calculate the Weissenberg number shown in Table and to define the slip regions in which the shear flow experiment was performed as specified in ref and added as a line to Figure , which serves as a theoretical demarcation between the transition zone and the strong slip region for this material. Experimental studies have shown that strong slip is independent of the MWD. , We note that the experimental point at 110.63 kPa (Figure ) falls exactly at the theoretical boundary between the transition and strong slip zones. In the experimental slip study, this point was identified as the last point in the transition zone, a truly remarkable agreement between theory and experiment considering the very broad MWDs that we are working with.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The tube-model parameters calculated for our material are used to calculate the Weissenberg number shown in Table and to define the slip regions in which the shear flow experiment was performed as specified in ref and added as a line to Figure , which serves as a theoretical demarcation between the transition zone and the strong slip region for this material. Experimental studies have shown that strong slip is independent of the MWD. , We note that the experimental point at 110.63 kPa (Figure ) falls exactly at the theoretical boundary between the transition and strong slip zones. In the experimental slip study, this point was identified as the last point in the transition zone, a truly remarkable agreement between theory and experiment considering the very broad MWDs that we are working with.…”
Section: Resultssupporting
confidence: 68%
“…The surface energy of the glass slides used in this study is 50 mJ/m 2 , classifying it as high energy . We remark that holes were also observed in the debris even on steel plates, which has a higher surface energy value of 60 mJ/m 2 (see Figure S2.2). The micrographs suggest that these holes could really be bare glass, and FTIR spectroscopy performed at these regions did not contain peaks expected for HDPE (see Figure S2.3).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations